Comparative analysis and characterization of expressed sequence tags in gilthead sea bream (Sparus aurata) liver and embryos - Sarropoulou, Elena (2014)
The gilthead sea bream (Sparus aurata) is one of the main European aquaculture products and a prospective model species for the Sparidae, which includes several other commercially important species. Future selective breeding of aquaculture stocks will be heavily underpinned by molecular genetic techniques, especially by marker-assisted selection (MAS). Gene marker resources in marine fish species, however, lag behind those of other agricultural animals, and only scanty information exists about the genetic source of phenotypic variation and the identity of quantitative trait loci (QTL). In order to develop molecular resources in gilthead sea bream, complementary DNA libraries were constructed from liver and mixed embryo and larval stages by unidirectional cloning. A long-read expressed sequence tag (EST) database was generated, containing 1394 cDNA clones representing 852 unique cDNA sequence-reads. Tissue-specific patterns of gene expression were determined when grouped using the proposal for characterizing cellular component put forward by the Gene Ontology consortium. Transcripts encoding cytoskeletal proteins were most abundant in the embryonic/larval library, while the most abundant transcripts in the liver library encoded secreted and extracellular proteins. Of both libraries, 505 clones were sequenced in both orientations (5Vand 3Vend sequencing), where 226 clones were determined as full-length sequence reads. Cluster analysis of 3Vend-sequenced clones from both libraries revealed that alternative polyadenylation signals were utilized, although no evidence of alternative splicing was found. We report for the first time for gilthead sea bream or any sparid a transcriptional analysis of two tissues and briefly consider the utility of ESTs for characterizing tissue-specific expression profiles. D 2004 Elsevier B.V. All rights reserved.